Halictus (Protohalictus) flaminii, the first Halictus described from Indonesia (Hymenoptera: Halictidae) - Brau, Thomas; Michez, Denis (Zootaxa, 2025)
The genus Halictus is a widespread and abundant bee group, especially in the Holarctic Region. A new species of Halictus from the subgenus Protohalictus, Halictus flaminii sp. nov., has been discovered out of the genus’ currently known range, from Lombok, Indonesia. This study provides a detailed description of the species and highlights its diagnostic features in comparison to closely related members of the subgenus in Asia.